Phenomena, gaps, and issues for neutronics modeling and simulation of FHRs. (January 2019) - Rahnema, Farzad; Diamond, David; Serghiuta, Dumitru; Burke, Paul
Abstract: On the path to deployment of any reactor, modeling tool verification and validation is a key step. Fluoride-Salt-Cooled High Temperature Reactors (FHR) pose challenges to neutronics modeling and simulation tools due to several design features of the reactor type. This paper presents a categorized list of phenomena that pose challenges to FHR modeling using current neutronics tools. These phenomena are presented in four categories: Fundamental Cross Section Data, Material Composition, Computational Methodology, and General Depletion. A short path forward for these phenomena is also presented. In addition, a discussion of the resulting gaps in current codes is presented.